2019
DOI: 10.1785/0120190088
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing Segmentation on the Wasatch Fault Zone: Impact on Seismic Hazard

Abstract: The multisegment Wasatch fault zone is a well-studied normal fault in the western United States that has paleoseismic evidence of recurrent Holocene surface-faulting earthquakes. Along the 270 km long central part of the fault, four primary structural complexities provide possible along-strike limits to these ruptures and form the basis for models of fault segmentation. Here, we assess the impact that the Wasatch fault segmentation model has on seismic hazard by evaluating the time-independent long-term rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…This presents a challenge when segmentation criteria based on shallow structures is used for assessing earthquake magnitudes for seismic hazard analyses (e.g. Field et al, 2009;Petersen et al, 2015;Valentini et al, 2019): where depth-dependent segmentation is not correctly identified, multi-segment and multi-fault ruptures such as those observed in the 2016 earthquakes in central Italy (Mw6.2,6.1 & 6.6) and…”
Section: Implications For Seismic Hazard Assessmentmentioning
confidence: 99%
“…This presents a challenge when segmentation criteria based on shallow structures is used for assessing earthquake magnitudes for seismic hazard analyses (e.g. Field et al, 2009;Petersen et al, 2015;Valentini et al, 2019): where depth-dependent segmentation is not correctly identified, multi-segment and multi-fault ruptures such as those observed in the 2016 earthquakes in central Italy (Mw6.2,6.1 & 6.6) and…”
Section: Implications For Seismic Hazard Assessmentmentioning
confidence: 99%
“…Since there are few long strike‐slip faults in the Walker Lane (Wesnousky et al., 2012), strike slip may occur mostly on shorter faults that are not capable of producing large (≥M7) earthquakes, and therefore slip in more frequent moderate earthquakes than in rarer larger ones (Anderson, 1979; Molnar, 1979). More frequent moderate earthquakes may pose greater hazard than fewer large earthquakes (Minson et al., 2020; Valentini et al., 2020). If missing strike slip is accommodated by moderate earthquakes that do not always rupture the surface (e.g., the 2020 Monte Cristo earthquake and dePolo, 1994), seismic hazard in the Walker Lane may be higher than estimates based solely on the paleoseismic record.…”
Section: Discussionmentioning
confidence: 99%
“…Further developments of the approach could integrate fault segmentation relaxation and the possible fault interactions into the seismic hazard model (e.g., Valentini et al, 2020;Verdecchia et al, 2018;Visini et al, 2020) and a better treatment of the uncertainties involved in the definition of the mechanical properties of broken speleothems and in the age record of speleoseismic events. F. Visini who helped us during the seismic noise measurements acquisition and discussed with us the seismic hazard results; D. Berardi who led us in the Cola Cave; F. Rizzo who helped us during the initial part of FEM modeling; S. Agostini for useful discussions on speleoseismology and for providing his papers collection.…”
Section: Discussionmentioning
confidence: 99%
“…Further developments of the approach could integrate fault segmentation relaxation and the possible fault interactions into the seismic hazard model (e.g., Valentini et al, 2020; Verdecchia et al, 2018; Visini et al, 2020) and a better treatment of the uncertainties involved in the definition of the mechanical properties of broken speleothems and in the age record of speleoseismic events.…”
Section: Discussionmentioning
confidence: 99%